Challenges and opportunities in implementing telemedicine within the primary healthcare system in Indonesia: A review - Syukran, Syukran; Rassanjani, Saddam (Innovation in Health for Society, 2026)
The utilization of telemedicine, or remote consultation, has emerged as a pivotal innovation in enhancing primary healthcare, a shift significantly accelerated by the pandemic's push toward digital health adoption. In Indonesia, integrating telemedicine into public health governance remains essential, particularly within public health centers (Puskesmas) and under the national health insurance (Jaminan Kesehatan Nasional [JKN]) scheme. This article examines the challenges and opportunities of implementing telemedicine within Indonesia’s primary healthcare ecosystem, focusing on policy design, regulatory frameworks, and administrative hurdles. Employing a qualitative narrative literature review approach, this study synthesized a total of 26 articles. The selected sources were evaluated using thematic and descriptive analysis to identify core implementation themes. The findings suggest that while telemedicine enhances healthcare access, administrative efficiency, and citizen engagement, critical governance challenges—such as digital inequality, data privacy concerns, and a lack of standardized implementation guidelines—persist. Government regulatory efforts during the pandemic only partially addressed these issues, meaning that long-term integration will heavily depend on strengthened institutional coordination and consistent policy frameworks. Ultimately, this research contributes to the broader discourse on public sector innovation and health governance by offering actionable policy recommendations to support the equitable and effective adoption of telemedicine across Indonesia Keywords: Healthcare policy, Indonesia, JKN, primary healthcare, public service